2019
DOI: 10.1007/s00586-019-06069-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological evaluation of cervical disc arthroplasty with 5-year follow-up: a prospective study of 384 patients

Abstract: Background Cervical total disc replacement was developed to avoid known complications of cervical fusion. The purpose of this paper was to provide 5-year follow-up results of an ongoing prospective study after implantation of cervical disc prosthesis. Methods Three hundred and eighty-four patients were treated using Mobi-C cervical disc (Zimmer Biomet, Troyes, France) and included in a prospective multicentre study. Routine clinical and radiological examinations were reported preoperatively and postoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…As expected, variations, and similarities in the biomechanical parameters stem from individual characteristics of the CDA itself. Acknowledging that any CDA's ultimate goal is to improve the patient's quality of life and act as a superior alternative to conventional ACDF, in what follows, these responses are interpreted in light of their design differences [1,4,6,24,25].…”
Section: Loading and Output Parametersmentioning
confidence: 99%
“…As expected, variations, and similarities in the biomechanical parameters stem from individual characteristics of the CDA itself. Acknowledging that any CDA's ultimate goal is to improve the patient's quality of life and act as a superior alternative to conventional ACDF, in what follows, these responses are interpreted in light of their design differences [1,4,6,24,25].…”
Section: Loading and Output Parametersmentioning
confidence: 99%
“…As a relatively rare complication of CDA, SF or class IV HO after CDA has been reported a few times since it was first reported in 2005. [14][15][16][17][18][19][20][21][22][23][24][25][26] The exact incidence of SF after CDA is still unclear, and it varies greatly in the literature. 26 Oh et al reported that the incidence of SF after CDA was 3.3% (2/60).…”
Section: Discussionmentioning
confidence: 99%
“…ACDF and CDA are the most commonly used surgical methods for the treatment of cervical degenerative diseases. [ 1 5 , 16 – 22 ] With the popular application of CDA, many common anterior cervical surgical complications, such as dysphagia and neck haematoma, have been reported, including prosthesis-related complications such as displacement. [ 14 , 15 ] In our study, one patient had a translucent area between the upper endplate of the prosthesis and the lower endplate of the vertebral body segment at the 3-month FU, but the patient did not complain of discomfort, and the size and position of the prosthesis were good.…”
Section: Discussionmentioning
confidence: 99%
“…Taking NSAIDs during the week and strict control of indications as well as an emphasis on intraoperative and perioperative management could reduce the incidence of HO. [ 22 , 24 ]…”
Section: Discussionmentioning
confidence: 99%